FOREIGN TEACHERS’ INSIGHTS REGARDING TEACHING “CONVERSATION” IN BOARDING SCHOOL: CHALLENGES AND STRATEGIES - Lestari Budianto; Iwan Hadi; Siti Zulaiha (Journey: Journal of English Language and Pedagogy, 2022)
Speaking becomes one of the English skills that should be developed. One of the schools that provided a special speaking class for the students is the Islamic Boarding Based Junior High School of Amanatul Ummah. Speaking class is labeled as a conversation subject in this school. In conversation class, the teachers are required to improve the students’ speaking skills. The teachers who handled a conversation subject were foreign teachers who used full English during teaching and learning. This paper investigates the foreign teachers’ perspectives of the teaching conversation subject. This research used qualitative method using descriptive approach. The participants of this research were two foreign conversation teachers of SMPBP and the participants were chosen using purposive sampling technique. The data were obtained through three instruments namely observation, semi-structured interviews, and documentation. The data then were analyzed using four stages namely data collection, data reduction, data display, and drawing conclusion. The result of this research showed that the foreign teachers faced several problems related to the students’ understanding, engagement, and teaching materials. The strategies used by the teachers were using digital tools, gestures, language simplifying, early materials preparation, and discussion with senior EFL teachers. This research contributes to the literature of English language teaching related to the teaching conversation subject.